PENGARUH PENGALAMAN AUDITOR, INDEPENDENSI DAN KEAHLIAN PROFESIONAL TERHADAP PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN - Juniaputri, Karina Khairunnisa; Anugerah, Rita; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to examine The Influence of Auditorâs Experience, Independence and Due to professional to Detection fraud. Object of this research are the accountant public offices in Pekanbaru, Padang, Palembang and Batam. There are fifty three questionnairs which are sent but, only forty nine questionnairs return. That data are analyzed by multiple regression method and SPSS program version 19. The variables were examined are Influence of Auditorâs Experience, Independence and Due to professional to Detection fraud. The results of this research showed that auditorâs experience has an effect on detection the fraud with 0,008 significance, independence has an effect on detection the fraud with 0,033 significance, and due to professional has an effect on detection the fraud with 0,018 significance. The results of this research also showed that coefficient determinant is 74,2%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study as, auditâs pressure, opportunity and others.Keywords: experience, independence, due to professional, and fraud